MENTAL HEALTH OUTCOMES OF ADULTS WITH COMORBIDITY AND CHRONIC DISEASES DURING THE COVID-19 PANDEMIC: A MATCHED CASE-CONTROL STUDY - Abu Sayeed; Satyajit Kundu; Md. Hasan Al Banna; Enryka Christopher; M. Tasdik Hasan; Musammet Rasheda Begum; Sukanta Chowdhury; Md Shafiqul Islam Khan (2020)
Background: Individuals with certain pre-existing chronic health conditions have been identified as a high-risk group for fatalities of .Therefore, it is likely that individuals with chronic diseases may worry during this pandemic to the detriment of their mental health.This study compares the mental health of Bangladeshi adults affected by chronic disease to a healthy, matched control group during the COVID-19 pandemic.Subjects and methods: A matched case-control analysis was performed with data collected from 395 respondents with chronic diseases and 395 controls matched for age, gender, and residence.Inclusion criteria for cases were respondents who self-reported having asthma, cardiovascular disease symptoms and/or diabetes.Respondents were recruited using an online survey, which included the DASS-21 measure to assess symptoms of stress, anxiety, and depression.Chi-square test, t-test, Fisher's exact test and a conditional logistic regression were performed to examine associations among variables.Results: The prevalence of anxiety symptoms and depression symptoms and the level of stress were significantly higher among cases (59%; 71.6%; 73.7%, respectively) than among controls (25.6%;31.1%;43.3%, respectively).Chi-square and t-test showed significant associations and differences between having chronic diseases and mental health outcomes.A conditional logistic regression showed that respondents with asthma, diabetes, cardiovascular disease symptoms, or any combination of these diseases had higher odds of exhibiting symptoms of stress, anxiety, and depression than healthy individuals.Conclusion: These results underscore a subpopulation vulnerable to mental health consequences during this pandemic and indicate the need for additional mental health resources to be available to those with chronic diseases.